Everyday creative a dangerous guide for making magic at work - Dixon, Mykel (Gildan Audio, 2020)
Upend your personal status quo and reclaim your natural creativity in every single action you takeEveryone claims to value creativity, and businesses are clamoring for disruptive thinking and innovation. Yet we often feel creatively stifled at work, because business processes seem to leave no room for real originality. In this climate, it takes a heroic effort to reclaim our status as independent thinkers, to bring meaning and joy to our work lives and to make lasting changes that will bring value to everyone around us. In Everyday Creative, culture and creative leadership expert Mykel Dixon reveals what's holding us back from our full creative potential and explains how we can reclaim our original, vibrant selves.Is your ability to think differently hindered by an unconscious view that creativity doesn't belong in the boardroom' It's an all-too-common mistake, but the truth is, creativity is fundamental for business growth and personal fulfillment. If you want to survive in the digital era, you need to pursue your own creative sensibilities and foster creativity in your team. This book shows that original thinking can shake things up, becoming the source of our competitive advantage and a key driver of sustainable success.